2021
DOI: 10.3390/v13091746
|View full text |Cite
|
Sign up to set email alerts
|

Unique Tropism and Entry Mechanism of Mumps Virus

Abstract: Mumps virus (MuV) is an important human pathogen that causes parotitis, orchitis, oophoritis, meningitis, encephalitis, and sensorineural hearing loss. Although mumps is a vaccine-preventable disease, sporadic outbreaks have occurred worldwide, even in highly vaccinated populations. MuV not only causes systemic infection but also has a unique tropism to glandular tissues and the central nervous system. In general, tropism can be defined by multiple factors in the viral life cycle, including its entry, interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Since it was shown that a trisaccharide containing α2,3-linked sialic acid at the cell surface acts as a receptor for MuV ( 2 , 3 ), the expression of SAs at the surface of guinea pig primary cell cultures from brain, testicles, lung, and kidney was measured. SAs were released by treatment with α2,3-sialidase (removes α2,3-sialyl groups) and Arthrobacter ureafaciens sialidase (removes the following sialyl groups at rate α2,6→α2,3→α2,8-linkage).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was shown that a trisaccharide containing α2,3-linked sialic acid at the cell surface acts as a receptor for MuV ( 2 , 3 ), the expression of SAs at the surface of guinea pig primary cell cultures from brain, testicles, lung, and kidney was measured. SAs were released by treatment with α2,3-sialidase (removes α2,3-sialyl groups) and Arthrobacter ureafaciens sialidase (removes the following sialyl groups at rate α2,6→α2,3→α2,8-linkage).…”
Section: Resultsmentioning
confidence: 99%
“…Mumps orthorubulavirus (MuV) belongs to the genus Orthorubulavirus of the family Paramyxoviridae , which includes enveloped, nonsegmented, negative-strand RNA viruses ( 1 ). Two MuV envelope glycoproteins, hemagglutinin-neuraminidase (HN) and fusion (F) protein, are involved in receptor binding and mediate membrane fusion with target cells ( 2 , 3 ). HN specifically recognizes sialic acid (SA)-containing glycoconjugate structures present on the host cells, preferring unbranched α2,3-sialylated glycans, which therefore play a key role in virus entry into host cells and infectivity ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Measles is still responsible for more than 100,000 deaths each year due to complications that can occur following infection, such as pneumonia and encephalitis [ 34 ]. Mumps affects at least 500,000 people each year [ 35 ] while the World Health Organization estimates that around 100,000 cases of congenital rubella syndrome occur every year [ 36 ]. An effective and safe vaccine against these three viral diseases is available.…”
Section: Vaccinomics: Factors Influencing the Immune Response To Vacc...mentioning
confidence: 99%
“…The role of the L protein in this complex is to trigger the RNA synthesis process, which consists of initiation, elongation, and termination. 8 The NP protein in MuV plays a role in the formation of the vRNA complex to avoid degradation and initiate the replication process. Inhibition of the NP protein's activity will disturb the initiation of the replication process by increasing the degradation of vRNA in MuV.…”
Section: Introductionmentioning
confidence: 99%